Heart and kidney transplant: should they be combined or subsequent?. (30th June 2020) - Melvinsdottir, Inga; Foley, David P.; Hess, Timothy; Gunnarsson, Sverrir I.; Kohmoto, Takushi; Hermsen, Joshua; Johnson, Maryl R.; Murray, David; Dhingra, Ravi
Abstract: Aims: End‐stage heart failure patients often present with severe kidney failure and have limited treatment options. We compared the clinical characteristics and outcomes among end‐stage heart and kidney failure patients who underwent combined heart and kidney transplant (HKTx) with those who underwent kidney transplant after heart transplant (KAH). Methods and results: All patients from 2007–2016 who underwent combined HKTx ( n = 715) and those who underwent KAH ( n = 130) using the United Network for Organ Sharing database were included. Kaplan‑Meier curves and Cox models compared survivals and identified predictors of death. Number of combined HKTx performed annually in United States increased from 59 in 2007 to 146 in 2016 whereas KAH decreased from 34 in 2007 to 6 in 2016. Among KAH patients, average wait time for kidney transplant was 3.0 years, time to dialysis or to kidney transplant after heart transplant did not differ with varying severity of kidney disease at baseline ( P for both >0.05). Upon follow‐up (mean 3.5 ± 2.7 years), 151 patients died. In multivariable models, patients who underwent combined HKTx had 4.7‐fold greater risk of death [95% confidence interval (CI) 2.4–9.4) than KAH patients upon follow up. A secondary analysis using calculation of survival only after kidney transplant for KAH patients still conferred higher risk for combined HKTx patients [hazard ratio (HR) 2.6 95% CI 1.33–5.15]. In subgroup analyses after excluding patients on dialysis (HR 3.99 95% CI 1.98–8.04) and analysis after propensity matching for age, gender, and glomerular filtration rate (HR 3.01 95% CI 1.40–6.43) showed similar and significantly higher risk for combined HKTx patients compared with KAH patients. Lastly, these results also remained unchanged after excluding transplant centres who performed only one type of procedure preferentially, i.e. HKTx or KAH (HR 4.70 95% CI 2.35–9.42). Conclusions: National registry data show continual increase in combined HKTx performed annually in the United States but inferior survival compared with KAH patients. Differences in patient characteristics or level of kidney dysfunction at baseline do not explain these poor outcomes among HKTx patients compared with KAH patients. Consensus guidelines are greatly needed to identify patients who may benefit more from dual organ transplants.